Foundations of digital signal processing theory, algorithms and hardware design - Gaydecki, Patrick (London, United Kingdom Institution of Engineering and Technology, 2004)
The book reviews developments in the following fields: digital signal processing; linear system toolbox; high-level computer programming; Delphi; electrical system; Fourier analysis; discrete Fourier property; Laplace space; Laplace transform; z-space; z-transform; digital filter design; signal sampling; analog-to-digital conversion; digital-to-analog conversion; finite impulse response filter; infinite impulse response filter; and adaptive filter.
Electronic reproduction.
Keywords: Signal processing -- Digital techniques; Electronic books